An Examination of the Degree of Complexity of Teacher Questions in English-Medium University Courses - David Lasagabaster; Aintzane Doiz (Universidad de La Sabana, 2024)
Research has demonstrated that questions are essential when teachers endeavor to foster students' comprehension and learning of the subject taught. However, there is a scarcity of studies on questioning practices in English-medium instruction (EMI) settings. In this study, we aim to fill this gap by focusing on the linguistic complexity of the questions put forward by EMI lecturers by paying particular heed to whether the disciplinary culture exerts any influence on the complexity of lecturers' questioning practices. The study was conducted at four public Spanish universities in which the classes delivered by nine EMI lecturers from three different disciplines (history, economics, and engineering) were recorded and analyzed. The statistical analyses performed found no significant differences in the lexical and syntactic complexity of the questions posed in the three disciplines, while language at the C level of the Common European Framework of Reference for Languages (CEFR) was conspicuous by its absence. These results lead us to conclude that if students are not widely exposed to language at the C level of the CEFR, oral language development and improvement may not be promoted in EMI courses. Therefore, EMI teacher training should be given more attention.